Chapter 30 Children’s Attitudes toward Older People: Current and Future Directions (2018)
The way we see the world is inevitably shaped by a number of factors such as culture, experience, language and values. Culture may be described as the customs, beliefs and values generally developed over time and experience, within a particular people or within a society. Language is one vehicle of cultural expression (Macionis and Gerber 2013). We understand the world by co-creating and co-constituting meaning and reality. The chapter begins with a brief presentation of the idea of social constructionism and ageism and then presents how one method of social construction, discourse, influences and mediates how we think, act and understand older people and how narratives can promote and privilege particular identities and consequently construct and reproduce ageism in society. Specific methodologies of discourse analysis are then introduced (Foucauldian discourse analysis and discursive psychology) to underpin the examination of data from research interviews of health care professionals (Phelan 2010), older people and their children (Ayalon 2015). Critical discourse analysis, such as Foucauldian discourse analysis